Exploring tourists' stress and coping strategies in leisure travel. (December 2020) - Zhu, Mingfang; Gao, Jie; Zhang, Linan; Jin, Shenglang
Abstract: Leisure travel can mediate daily stress, but also provoke stress. Tourists experience multiple stress during their vacations. The aim of this study was to identify what types of stress tourists encounter during their travel experiences and what strategies they use to cope with stress. Using semi-structured interviews and participant observation, the study findings reveal that tourists encounter four major types of stress (i.e., service-provider-related stress, traveler-related stress, travel-partner-related stress, and environment-related stress) during their vacations and use many strategies (i.e., problem-focused and emotion-focused coping) to cope with stress. These findings not only contribute to tourism research by documenting specific types of stress in the travel context and exploring new insights into ways of coping with stress, but also provide suggestions for how tourism and hospitality professionals should modify programs/experiences in response to tourists' stress and the need to cope with stress during travel experiences. Highlights: This study examines how leisure travel provoke stress, instead of its mediating role. The stress-coping construct enhances the study of tourists' stress during vacation. Chinese tourists encounter four major types of stress. The special cultural context of China affects coping strategies. This study uncovered many strategies (e.g., posting on Wechat) to cope with stress.